2019
DOI: 10.1111/1365-2745.13294
|View full text |Cite
|
Sign up to set email alerts
|

How neighbourhood interactions control the temporal stability and resilience to drought of trees in mountain forests

Abstract: Over the coming decades, the predicted increase in frequency and intensity of extreme events such as droughts is likely to have a strong effect on forest functioning. Recent studies have shown that species mixing may buffer the temporal variability of productivity. However, most studies have focused on temporal stability of productivity, while species mixing may also affect forest resilience to extreme events. Our understanding of mechanisms underlying species mixing effects on forest stability and resilience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 72 publications
3
33
1
Order By: Relevance
“…Our results are in contrast to findings from temperate forests, where Jucker, Bouriaud, Avacaritei, Dǎnilǎ, et al () demonstrated the strongest decline in biodiversity effects (relative to community tree species richness) during dry years for species associated with the lowest drought tolerance. Similarly, the proportion of heterospecific neighbours was shown to positively affect drought resilience of drought‐tolerant species ( Quercus pubescens ), while a neutral ( Fagus sylvatica ) and negative ( Abies alba ) effect was evident for less drought‐tolerant species (Jourdan et al, ). These differences might be largely attributed to differences in biomes (level of tree species diversity, climate and soil conditions).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in contrast to findings from temperate forests, where Jucker, Bouriaud, Avacaritei, Dǎnilǎ, et al () demonstrated the strongest decline in biodiversity effects (relative to community tree species richness) during dry years for species associated with the lowest drought tolerance. Similarly, the proportion of heterospecific neighbours was shown to positively affect drought resilience of drought‐tolerant species ( Quercus pubescens ), while a neutral ( Fagus sylvatica ) and negative ( Abies alba ) effect was evident for less drought‐tolerant species (Jourdan et al, ). These differences might be largely attributed to differences in biomes (level of tree species diversity, climate and soil conditions).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, BPRs at the local neighbourhood scale should become stronger during periods of water deficits, meaning that the relative importance of biodiversity effects increases during drought (Figure a,b). The few evidence on climate–growth relationships in response to local neighbourhood conditions comes from observational studies performed in less diverse temperate forests with a limited taxonomic tree diversity (Jourdan, Kunstler, & Morin, ), and most of these studies accounted for neighbourhood diversity using a contrast of neighbourhood composition (conspecific vs. heterospecific neighbours; Mölder & Leuschner, ; Vitali, Forrester, & Bauhus, ) or neighbourhood competition (intraspecific vs. interspecific competition; Aussenac, Bergeron, Gravel, & Drobyshev, ). Similarly, one recent experimental study explored drought resistance of tropical tree seedlings in response to neighbourhood composition (conspecific vs. heterospecific neighbours; O’Brien, Reynolds, Ong, & Hector, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the large variability in site conditions covered by both types of stands (Supplement Table 1) and the large number of trees sampled made the comparison reliable and representative of European beech's growth trends in mountain regions. Nevertheless, the identified mixing effect on growth trends could be partly masked by the different identities of the admixed species, as species interactions vary among different beech mixtures (del Río et al 2014;Pretzsch and Forrester 2017;Jourdan et al 2020).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Thus, in this range, the relation between sensitivity and forest cover before the tipping point is weak and the forestcover fraction remains almost stable. Possible mechanisms are that forests can resist drought through, for instance, investing more carbohydrates into root growth for higher soil water availability 32 , increase stomatal closure during the middle of the day for less transpiration, thus increasing water-use efficiency (WUE) 33 and leading to a more stable forest cover even during drought events 34 . The assumption of stable vegetation cover under drought is also supported by satellite-observed dry-season green up in Amazonian forest.…”
Section: Implications On Amazonian Forest Diebackmentioning
confidence: 99%